Análisis y perspectivas del clima organizacional en el Municipio de Medellín - 1996 - - -CEO-, Centro de Estudios de Opinión; Ruiz Restrepo, Jaime (La Sociología en sus Escenarios, 2009)
Abstract. In 1996, the University of Antioquia, through C.I.C.A. (Research center and Administrative Consultancies, of the Faculty of Economic Sciences) it developed for the Municipality of Medellín, and in individual for the Secretariat of Administrative Services, the titled study “diagnosis and implantation of a system of qualification for the human development of the employees and workers of the municipality of Medellín”. In their totality, the results and analyses of all the process of investigation, discussion and formulated planning of the proposals and alternatives there, aimed essentially at the elucidation of the conditions of the surroundings that acted on the motivations, stimuli and desestímulos that affected the civil employees who were to the service of the municipal administration and which, therefore, they would serve like indicators of the movements necessary to make to optimize the yields. Resumen. En 1996, la Universidad de Antioquía, a través del C.I.C.A.(Centro de Investigaciones y Consultorías Administrativas, de la Facultad de Ciencias Económicas) desarrolló para el Municipio de Medellín, y en particular para la Secretaría de Servicios Administrativos, el estudio titulado “diagnóstico e implantación de un sistema de capacitación para el desarrollo humano de los empleados y trabajadores del municipio de Medellín”. En su totalidad, los resultados y análisis de todo el proceso de indagación, discusión y planeación de las propuestas y alternativas formuladas allí, apuntaban esencialmente al esclarecimiento de las condiciones del entorno que actuaban sobre las motivaciones, estímulos y desestímulos que afectaban a los funcionarios que estaban al servicio de la administración municipal y que, por tanto, servirían como indicadores de los movimientos necesarios de realizar para optimizar los rendimientos.